Higher Circulating Vitamin D Levels Are Associated With Decreased Migraine Risk: A Mendelian Randomization Study - Niu, Peng-Peng; Wang, Xue; Xu, Yu-Ming (Frontiers in Nutrition, 2022)
Background: Evidence showed the supplementation of vitamin D might have beneficial effects for migraine patients. We aimed to investigate the causal effects of serum vitamin D levels on migraine risk using two-sample Mendelian randomization (MR) method. Methods: A total of 184 independent genetic instruments for serum vitamin D levels were selected from a study in 417,580 Europeans from UK biobank. Six variants from an independent study were obtained to perform replication analysis. Summary-level data for migraine were obtained from three studies with 48,975 migraine cases, 28,852 migraine cases and 10,536 migraine cases respectively. Results: The estimated odds ratios (ORs) per standard deviation increase in circulating vitamin D levels based on the three migraine datasets were 0.948 (95% CI = 0.883–1.016, p = 0.133), 0.902 (95% confidence intervals [CI] = 0.825–0.986, p = 0.023), and 0.880 (95% CI = 0.786–0.984, p = 0.025) respectively. Using pooled migraine summary data with no sample overlap, MR analysis showed per standard deviation increase in circulating vitamin D levels was significantly associated with a decreased migraine risk (OR = 0.916, 95% CI = 0.859–0.977, p = 0.008). Multivariable MR analyses, sensitivity analyses and replication analysis confirmed the association. MR analyses showed similar estimates for migraine with aura and migraine without aura but with wider 95% CIs. Mediation analysis showed the effect of vitamin D on migraine risk via pathway of serum calcium was corresponding to an OR of 1.003 (95% CI = 1.001–1.005) and a proportion mediated of 3.42%. The reverse MR analysis showed migraine might not affect vitamin D levels. Conclusion: This two-sample MR study showed genetically determined increased circulating vitamin D levels are associated with decreased migraine risk. The effect seems consistent across different migraine subtypes. In addition, the role of serum calcium in mediating the association between vitamin D and migraine is negligible. Future large well-designed randomized trials are warranted to assess the effects of vitamin D supplementation for migraine patients, especially in those with vitamin D deficiency.